APPLICATION OF E-NETWORKS FOR MODELING ALGORITHMS FOR CONTROL OF A SECTION OF A TELECOMMUNICATION NETWORK - Bukhanko, A. N.; Bezruk, V. M.; Duravkin, E. V. (Radio Electronics, Computer Science, Control, 2024)
In the article the simulation models of managing agent’s algorithms based on the chosen method of Е-networks for the area of difficult telecommunication network are developed.